Transport properties and enhanced figure of merit of quantum dot-based spintronic thermoelectric device. (12th July 2018) - Zubov, Yu D; Ilinskaya, O A; Krive, I V; Krokhin, A A
Abstract: Transport properties of quantum dot-based thermoelectric device with magnetic leads placed in external magnetic field are considered. The exact expressions for the thermoelectric coefficients are obtained by the equation of motion method, assuming noninteracting electrons. It is shown that at the maximum power mode the figure of merit of the proposed spintronic device is several times higher than that of a device with unpolarized electrons. The influence of electron–electron interaction on the figure of merit is analyzed and it is shown that in the limit of strong Coulomb repulsion the optimal thermoelectric performance predicted for noninteracting electrons is restored.